The global forest above-ground biomass pool for 2010 estimated from high-resolution satellite observations - Santoro, Maurizio (2022)
Funding Information: We are thankful to the GlobBiomass project team and Frank Martin Seifert (ESA) for valuable suggestions and stimulating scientific discussions. We are thankful to Takeo Tadono (JAXA EORC), Masato Hayashi, (JAXA EORC), Kazufumi Kobayashi (RESTEC), Åke Rosenqvist (soloEO), and Josef Kellndorfer (EBD) for support with the use and interpretation of the ALOS PALSAR mosaics. Support by the CCI Land Cover project team, in particular Sophie Bontemps (UCL), is greatly acknowledged. The help from Martin Jung (MPI-BGC) in feature selection and Ulrich Weber (MPI-BGC) for data processing for the GSV-to-AGB conversions is greatly acknowledged. Forest inventory data for the validation of the AGB map were made available by, among others, Ben de Jong; the Prince Edward Island Department of Communities, Land and Environment – Forests, Fish and Wildlife Division; and the Nova Scotia Department of Natural Resources. Inventory data were also provided by the Sustainable Landscapes Brazil project supported by the Brazilian Agricultural Research Corporation (EMBRAPA), the US Forest Service, the USAID, and the US Department of State. We thank the three anonymous reviewers, contributors to the short comments, Geerten Hengeveld, and Jérôme Chave for reviewing and improving the manuscript. Funding Information: Financial support. This research has been supported by the European Space Agency (ESRIN contract no. 4000113100/14/I-NB) and the Russian Science Foundation (grant no. 19-77-30015). Funding Information: Acknowledgements. The National Centre for Earth Observation was supported by the UK Natural Environment Research Council. The FOS data collection for Russia was performed within the framework of the state assignment of the Center for Forest Ecology and Productivity of the Russian Academy of Sciences (no. AAAA-A18-118052590019-7). The Russian ground data preparation and pre-processing were financially supported by the Russian Science Foundation (project no. 19-77-30015). Publisher Copyright: © 2021 Maurizio Santoro et al.